Teenagers and stuttering management: are they ready? - Zebrowski, Patricia (Henry Stewart Talks, 2016)
Motivation, Readiness can change, Motivational interviewing, The stages of change model, Decisional balance, Self-efficacy, Staging algorithm: stuttering management, UISPEAKS program for teens, Therapy map